Performance and Vibration Analysis of Electric Outboard Propulsion using Propeller Variations Based on Experiment - Iswantoro, Adhi; Raharjo, Juniono; Iwangsa Sima, Yonathan (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
The demand for electric vehicles, including electric outboard propulsion for small ship, is on the rise due to growing environmental concerns. To optimize the performance of electric outboards, propeller selection, particularly propeller pitch, is crucial. This research evaluated the impact of varying propeller pitches 8, 9 and 12 degrees on the performance of an electric outboard propulsion. Through both laboratory and field tests, measurements of water flow velocity and thrust, energy consumption, boat speed, and vibration levels were conducted. The objective was to identify the optimal propeller pitch that maximizes propulsive efficiency and minimizes energy consumption. Results indicated that a propeller pitch of 8 degrees produced the highest water flow velocity, implying the greatest thrust. Field tests corroborated these findings, with the 8-degree pitch achieving an average speed of 10 km/h and a roundtrip time of 3.48 minutes. However, the 8-degree pitch also exhibited the highest energy consumption at 0.31366 kWh. Vibration levels were minimal across all pitches, suggesting no structural damage. These findings hold significant implications for the design and selection of electric propulsion systems in small ship, especially for patrol boats.